Hubungan Pemanfaatan Smartphone Sebagai Sumber Belajar dengan Prestasi Belajar Siswa Sekolah Dasar - Jamun, Yohannes Marryono; Ntelok, Zephisius Rudiyanto Eso; Jediut, Mariana (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The development of information technology, particularly smartphones, has significantly changed the educational landscape. The high accessibility and variety of learning applications have made smartphones a popular learning tool among students. Research shows that the proper use of smartphones can enhance students' motivation, engagement, and academic achievement. However, excessive use can have negative effects, such as concentration problems and declining performance. This study aims to examine the relationship between the use of smartphones as a learning resource and the academic achievement of elementary school students. This research uses a quantitative-descriptive method, analyzing the relationship between smartphone use as a learning resource and the academic performance of grade V students at Sita-Kaca SDI. Hypothesis testing was conducted using simple linear regression. The sample of this study consists of 21 fifth-grade students, with purposive sampling technique. The research conducted at Sita-Kaca SDI, in the district of Rana Mese, East Manggarai Regency, shows a significant and positive impact. This is demonstrated by a correlation coefficient of 8.4% between smartphone use and academic achievement at a two-tailed significance level of 0.05. The value of r = 0.289 is positive. This means that the higher the use of smartphones in the learning process, the higher the students’ academic performance. The use of smartphones has an impact on student achievement. The results of this study show that smartphone use is actively involved in the learning activities, contributing 8.4%. This implies that 91.6% of other factors not studied in this research affect students' academic performance.